Rancangan Tata Letak Fasilitas Produksi Tepung Mocaf Menggunakan Metode BLOCPLAN - Ahmad Ghozi; Didik Hermanuadi (Jurnal Teknik Pertanian Terapan, 2023)
The purpose of designing the layout of the facility is to make effective use of space, minimize material handling, expedite the production process and increase the effectiveness of the use of labor. This research method is to use the BLOCPLAN method. This method can help design the layout of the mocaf flour production facility by providing an alternative layout by taking into account the space to be mapped and the inter-departmental/room interrelationships contained in the Activity Relationship Chart (ARC). The results obtained are a factory capacity of 2.5 tons/day, the number of machines needed is 13, the area needed for the mocaf flour factory area is 1.107 m2 with 8 departments/rooms. There are 20 alternative layouts resulting from the BLOCPLAN software, the proposed layouts are selected based on the R-Score value close to 1, namely layout 19.